The Utility of Constructivist Grounded Theory in Critical Policy Analysis - Tebogo B. Sebeelo (International Journal of Qualitative Methods, 2022)
Constructivist grounded theory (CGT) has gained traction as a popular method across various fields in both the social and natural sciences. Its acclaim lies in its constructivist and pragmatist heritages that emphasize flexibility, co-construction and subjectivity. Despite its general appeal, CGT remain largely unexplored in the area of critical policy analysis. Using data from an alcohol policy dissertation in Botswana, this paper applies CGT to What’s the Problem Represented to Be (WPR), a Foucauldian-inspired poststructural policy analysis framework. WPR served as a framework while CGT provided strategies to do it. The paper demonstrates the utility of CGT as a useful strategy in critical policy analysis. The practice of CGT aligns with critical policy studies that consider subjectivity, temporality and reject value-free enquiry. Furthermore, CGT aligns with policy analysis studies that explicate human experience and meanings. The implications of deploying CGT to critical policy analysis are outlined in the paper.